INTEGRATING ARTIFICIAL INTELLIGENCE IN EDUCATION: TRANSFORMING LEARNING AND DRIVING INNOVATION (Contemporary Journal of Social Science Review, 2025)
The implementation of Artificial Intelligence (AI) in education is ushering in a rapid transformation of traditional learning processes, course planning, and administrative tasks. This study identifies various roles that AI plays in supporting educational interventions, particularly in enhancing students' learning experiences and reducing teachers' workloads. Data was collected from fourty participants, including students and faculty, across different higher education institutions and policymakers through purposive and convenient sampling techniques. The research findings indicate that while AI serves as a significant driver of innovation, its effective integration into education remains a crucial challenge. The study highlights that one of the most frequently cited benefits of AI is its ability to create personalized learning experiences and adaptive response interfaces. In terms of instructional improvement, participants highlighted the effectiveness of AI in automating tasks such as grading, planning, and academic analytics. This research contributes to the understanding of the impact that AI technologies are having on the education system. It offers recommendations for strategic actions for educators, policymakers, and organizations to foster collaboration between teachers and AI, promote sound data stewardship, and encourage the acceptance and understanding of AI.